Utilizing Trigger Films to Enhance Communication Skills of Home Care Clinicians. (July 2016) - Brennan-Cook, Jill; Molloy, Margory A.
Abstract : The purpose of this article is to describe an innovative method to help home care clinicians better communicate with older adults experiencing normal physiologic changes that impact their ability to communicate effectively. Developmental changes such as hearing, speech, vision, and cognition profoundly impede an older adult's ability to communicate with others, potentially undermining the quality of care delivered. The use of trigger films as an educational intervention can assist home care clinicians to improve communication with their patients. Trigger films are 2- to 4-minute video clips that end abruptly, encouraging learners to analyze clinical situations in a safe environment, such as a staff conference room. Trigger films are easy to make with the use of a smart phone and two staff members portraying the role of home care clinician and patient. Allowing discussion after viewing the trigger film places clinicians in an active learning role, thus fostering the sharing of ideas and best practice. Addressing age-related barriers to communication with this modality serves to improve patient interaction and healthcare outcomes. The use of trigger films is another tool that empowers the clinician to provide improved care for patients with communication deficits.